Anorectal syphilis presenting at Crohn's disease: A case report - Hannah E Myers; Kevin Pennycook; Christopher Buckley (Wolters Kluwer Medknow Publications, 2023)
This article reports on a case of anorectal syphilis in a 54-year-old man with a history of Crohn's disease. The patient began experiencing a new onset perianal rash approximately when his medication regimen for Crohn's disease was switched from sulfasalazine to mesalamine. There was no reported history of new sexual partners or sexually transmitted infection exposures. Chief differential at this time included Cutaneous Crohn's disease, Lichen Planus, Extramammary Paget's Disease, and Porokeratosis Ptychotropica; however, shave biopsy results revealed unexpected syphilis. There is only one other reported case of syphilis presenting as Crohn's disease, but the incidence of syphilis has been rapidly increasing within the last decade. A high index of clinical suspicion is needed to properly diagnose syphilis, even with a lack of sexual history, for new onset genital lesions.